Gravitational wave speed: implications for models without a mass scale - Nersisyan, Henrik; Lima, Nelson A.; Amendola, Luca (Arxiv, 2018)
The recent report that the gravitational wave speed equals the light speed puts strong constraints on the anisotropic stress parameter of many modified gravity models, a quantity that is directly observable through large-scale structure. We show here that models without a mass scale completely escape these constraints. We discuss a few relevant cases in detail: Brans-Dicke theory, nonlocal models, and Galileon Lagrangian.
Gesehen am 07.03.2018